Aedes aegypti on Madeira Island (Portugal): genetic variation of a recently introduced dengue vector - Seixas, Goncalo; Salgueiro, Patricia; Silva, Ana Clara; Campos, Melina; Spenassatto, Carine; Reyes-lugo, Matias; Novo, Maria Teresa; Ribolla, Paulo Eduardo Martins; Pinto, Joao Pedro Soares Da Silva; Sousa, Carla Alexandra (Instituto Oswaldo Cruz, Ministério da Saúde, 2013)
The increasing population of Aedes aegypti mosquitoes on Madeira Island (Portugal) resulted in the first autochthonous dengue outbreak, which occurred in October 2012. Our study establishes the first genetic evaluation based on the mitochondrial DNA (mtDNA) genes [cytochrome oxidase subunit I (COI) and NADH dehydrogenase subunit 4 (ND4)] and knockdown resistance ( kdr ) mutations exploring the colonisation history and the genetic diversity of this insular vector population. We included mosquito populations from Brazil and Venezuela in the analysis as putative geographic sources. The Ae. aegyptipopulation from Madeira showed extremely low mtDNA genetic variability, with a single haplotype for COI and ND4. We also detected the presence of two important kdr mutations and the quasi-fixation of one of these mutations (F1534C). These results are consistent with a unique recent founder event that occurred on the island of Ae. aegyptimosquitoes that carry kdr mutations associated with insecticide resistance. Finally, we also report the presence of the F1534C kdr mutation in the Brazil and Venezuela populations. To our knowledge, this is the first time this mutation has been found in South American Ae. aegypti mosquitoes. Given the present risk of Ae. aegypti re-invading continental Europe from Madeira and the recent dengue outbreaks on the island, this information is important to plan surveillance and control measures.
Keywords: Aedes aegypti; dengue; knockdown resistance; mtDNA